Pašušvio šnektos izoliuotų balsių spektrų tyrimas - Kazlauskaitė, Rūta (Kalbotyra, 2002)
The article examines the spectra of isolated vowels, their acoustical features, articulation and their relationship with the corresponding vowels of the subdialects of Akmenė, Eržvilkas, Lukšiai, Kučiūnai, and D. Jones’ cardinal vowels.The system of the isolated vowels of the Pašušvys subdialect is the closest to the system of the Lukšiai subdialect, what is especially true of the vowels [a.], [a.], [a] which are lower as compared with the same vowels of the other subdialects.The distance between the articulation place of separate vowels of the Pašušvys subdialect is small: the back labialised [u.], [u.], [u], [o.] are pronounced almost in the same back place of the mouth (values of F2 are similar), the front [e̤.] [ε̣.], [i.], [i], [ẹ] differ a little from each other by the vertical movement of the tongue and degree of the openness of the mouth. The [o.] is the most back and [e̤.], [ε̣.] are high vowels. Compared with the very open [i̲], [u̲] of the Raseiniai sub dialect, Pašušvys analogic vowels are more close, but more open than half-long and long ones. The long [a.], [æ.] are higher and closer than the corresponding half-long [a.] [æ.]. The reason for this must be the surviving traces of nasalisation.The spectral analysis and the acoustic data allow us to claim that the isolated vowels of the Pašušvys subdialect are more similar to the secondary rather than to primary cardinal vowels. Neither the extreme front nor the extreme back articulation is characteristic of the vowels of the subdialect.